PENERAPAN PROGRAM SEKOLAH SAKA RELIGI (SELASA KAMIS RELIGI) DALAM PENGEMBANGAN LITERASI AL-QUR’AN DI SD NEGERI 1 GARUNG WONOSOBO - Mukhammad Nuzunul Rozaqi; Ahmad Khoiri; Hidayatu Munawarah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the implementation of the SAKA RELIGI School Program (Tuesday–Thursday Religious Activities) in developing Qur’anic literacy at SD Negeri 1 Garung Wonosobo, as well as to identify the supporting and inhibiting factors in its implementation. The study employed a qualitative approach using a descriptive method. The research subjects included the principal, Islamic Education teachers, and fifth-grade students. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the SAKA RELIGI Program is implemented regularly through Qur’an recitation activities, memorization of short surahs, tajwid instruction, and the internalization of Qur’anic values. This program has been shown to improve students’ Qur’an reading abilities and to foster religious attitudes such as discipline, responsibility, and politeness. Supporting factors include the principal’s support, the active role of teachers, and a religious school environment. Meanwhile, inhibiting factors include limited time, differences in students’ reading abilities, and a lack of parental assistance at home.